Penapisan dan Karakterisasi Bakteri Selulolitik Termofilik Sumber Air Panas Sungai Medang, Kerinci, Jambi - Uci Mela Sari; Anthoni Agustien; - Nurmiati (Universitas Andalas, 2012)
A study on screening and characterization odf cellulolytic thermophylic bacteria from Sungai Medang hot spring was conducted on May to June 2012 using purposive sampling methods. This study aimed to find a cellulolytic thermophylic bacterium and to analyze its cellulolyties. Twenty eight cellulolytic thermophylic bacteria were isolated from Sungai Medang hot springs. The highest enzymatic activity (amylolytic and proteolytic activity) was shown by isolate MII2.1 from a location at which the temperature was 78oC. This isolate was characterized as an aerobic bacterium, gram negative and non motile. The form of colony was a circular margin, smooth shiny surface and elevation flat.Keywords: amylolytic, bacterium, cellulolytic, proteolytic, thermophylic